2014
DOI: 10.1186/1742-4755-11-36
|View full text |Cite
|
Sign up to set email alerts
|

Fertility intentions among HIV positive women aged 18–49 years in Addis Ababa Ethiopia: a cross sectional study

Abstract: BackgroundGiven the degree of HIV epidemic among women and the current antiretroviral therapy (ART) scale up in Ethiopia; considering the issue of fertility is vital to ensure the delivery of integrated reproductive health along with prevention services provided to positive women. This study was aimed to assess fertility intentions of women living with HIV attending public health institutions (hospitals & health centers) in Addis Ababa, Ethiopia.MethodsInstitution based cross sectional survey was conducted, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
51
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 24 publications
13
51
1
Order By: Relevance
“…Similar studies of HIV-infected women aged 18 to 49 in Ethiopia and Ghana identified intention proportions of 44% (Asfaw and Gashe, 2014) and 58% (Gyimah et al, 2015), respectively. Past research among HIV-infected South African women also reported childbearing intention that was lower than identified in our study: a 45% proportion of intention was found among a Cape Town cohort aged 25 to 34 (Cooper et al, 2009), and 30% proportion was identified in a cohort aged 18 to 44 in Soweto (Kaida et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Similar studies of HIV-infected women aged 18 to 49 in Ethiopia and Ghana identified intention proportions of 44% (Asfaw and Gashe, 2014) and 58% (Gyimah et al, 2015), respectively. Past research among HIV-infected South African women also reported childbearing intention that was lower than identified in our study: a 45% proportion of intention was found among a Cape Town cohort aged 25 to 34 (Cooper et al, 2009), and 30% proportion was identified in a cohort aged 18 to 44 in Soweto (Kaida et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
“…This is similar to prior findings among South African women (Kaida et al, 2011) and in the aforementioned meta-analysis (Berhan and Berhan, 2013). Some studies, however, have found being on ART to be correlated with increased childbearing intention (Abbawa et al, 2015; Asfaw and Gashe, 2014; Cooper et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although they dramatically decrease the chances of sexual and perinatal HIV transmission, such techniques are rarely used in sub-Saharan Africa. Moreover, there is a growing body of evidence indicating that the prevalence of HIV infection might decrease but does not eliminate fertility intentions 1, 3, 14, 15. The management of HIV-infected pregnant women poses specific challenges for the prevention of mother-to-child transmission of HIV (PMTCT) and horizontal transmission in lower-income countries 16, 17.…”
Section: Introductionmentioning
confidence: 99%